Extreme cities the peril and promise of urban life in the age of climate change - Dawson, Ashley 1965- (Verso, 2019)
How will climate change affect our lives? Where will its impact be most deeply felt? Are we doing enough to protect ourselves from the coming chaos? In Extreme Cities, Ashley Dawson argues that cities are ground zero for climate change, contributing the lion's share of carbon to the atmosphere, while also lying on the frontlines of rising sea levels. Dawson offers an alarming portrait of the future of urban life that describes the efforts of urban residents to relocate, Holland's models for defending against the seas, and the development of New York City before and after Hurricane Sandy. Our best hope lies not with fortified sea walls, he argues, but with urban movements already fighting to remake our cities in a more just and equitable way. As much a harrowing study as a call to arms, Extreme Cities is a necessary read for anyone concerned with the thread of global warming.